The new mothers' little helpers: medicalization, victimization, and criminalization of motherhood via prescription drugs. Issue 8 (3rd August 2019) - Smirnova, Michelle; Gatewood Owens, Jennifer
ABSTRACT: In order to understand the relationship between nonmedical prescription drug use, gender, and crime, interviews were conducted with 40 incarcerated women who self-identified as nonmedical Rx users. Of the women we interviewed, 70% were prescribed Rx drugs from their doctors to aid in recovery from cesarean section childbirth deliveries, treat postpartum depression, or for mental or physical health problems associated with childhood abuse and victimization. These women subsequently discovered that these pills also helped them cope with the stresses of caretaking and keeping the family together, particularly when experiencing intimate partner violence and prolonged poverty. Women were motivated to use Rx drugs in order to be a "good" mother, as defined by medical and cultural discourse; however, despite positive intentions, prolonged nonmedical use often hindered the realization of these ideals and ultimately resulted in their criminalization, incarceration, and separation from their children.